1975
DOI: 10.1098/rspb.1975.0152
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of lead by inhalation of motor exhaust

Abstract: Tetraethyl lead was labelled with 203 Pb, added to petrol, and burnt in an engine. The exhaust aerosol was inhaled by volunteers, usually after it had been stored in a box, but in a few experiments directly, a few metres downwind of the engine. The percentage deposition in the lung, uptake to blood and excretion of the labelled lead were measured. The percentage deposition in the lung depended on the length of the respiratory cycle. For a 4 s cycle (15 breaths/min) the deposition was 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Reports and images of particle collapse are commonly found in the literature (Chamberlain et al, 1975;Colbeck et al, 1997;Hallett et al, 1989;Huang et al, 1994;Jimenez et al, 2003;Mikhailov et al, 2006;Nelson, 1989;Weingartner et al, 1995;Weingartner et al, 1997;Zuberi et al, 2005) dating as far back as 1975. In a study of uptake of lead by inhalation of motor exhaust, Chamberlain et al (1975) observed a more "homogenous" structure of previously chain aggregate carbonaceous material after it was exhaled from a humid human lung. It was reported that this was similar to the effect on chain aggregate-type aerosol that was drawn through a humidifier.…”
Section: Particle Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…Reports and images of particle collapse are commonly found in the literature (Chamberlain et al, 1975;Colbeck et al, 1997;Hallett et al, 1989;Huang et al, 1994;Jimenez et al, 2003;Mikhailov et al, 2006;Nelson, 1989;Weingartner et al, 1995;Weingartner et al, 1997;Zuberi et al, 2005) dating as far back as 1975. In a study of uptake of lead by inhalation of motor exhaust, Chamberlain et al (1975) observed a more "homogenous" structure of previously chain aggregate carbonaceous material after it was exhaled from a humid human lung. It was reported that this was similar to the effect on chain aggregate-type aerosol that was drawn through a humidifier.…”
Section: Particle Collapsementioning
confidence: 99%
“…It was reported that this was similar to the effect on chain aggregate-type aerosol that was drawn through a humidifier. Chamberlain et al (1975) postulated that the chain aggregate particle collapses in wet air due to the discharge of electrostatic forces. A later explanation cited by Hallett et al (1989) and Weingartner et al (1995Weingartner et al ( , 1997 is that condensation of water in small angle cavities of the branched structure leads to capillary forces that collapse the asymmetric particle.…”
Section: Particle Collapsementioning
confidence: 99%
“…Only 1-2% of 50 jig of lead as Pb(NO3) 2 dried onto a personnel sampler filter went into solution after 72 h of incubation in simulated lung fluid at room temperature (approximately 23 0C). In contrast, we know that persons exposed by inhalation to lead oxide aerosol have shown dissolution and movement into blood of about 50% of the lead initially deposited in the lung (Ch75).…”
Section: Dissolution Of Aerosol Lead In Simulated Lung Fluidmentioning
confidence: 95%
“…These depend on particle density, size, and shape as well as particle solubility and the rate and depth of respiration [National Academy of Sciences, 19721. It has been estimated that for most common lead aerosols of mixed particle size between 30% and 50% of the total inhaled lead mass will be retained in the alveolar region and completely absorbed [Kehoe, 1961;Task Group on Lung Dynamics, 1966;National Academy of Sciences, 1972;Chamberlain et al, 1975;Ratcliffe, 19811. The larger particles deposit in the nose, throat, and upper airways, where they are cleared to the gastrointestinal tract by ciliary action [Muir, 19721. CPA assumed that all lead particulates not deposited and absorbed through the alveoli are ingested.…”
Section: Kinetic Model To Estimate Blood Leadmentioning
confidence: 99%